(untitled) (Pedagogy of Higher and Secondary Education, 2022)
An author offers a postulate about possibility of imitation of arbitrary smooth curve by a line with the tsyrkuVnymy interfaces. The method of construction of decorative compositions having in the composition lines with the tsyrkulnymy interfaces is developed, which passed out the test on the artistically-graphic faculty of the Kryvorozhskogo state pedagogical university.